Maturation Assessment of Graffian Follicle in Female Mice under Immobilization, Hunger and Noise Stress - Yousaf, Maria; Ayesha Asad; Kishwar Naheed; Humaira Ali; Hina Kundi; Sadia Muzaffar (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the effects of immobilization, noise and hunger stress on the graffian follicle diameter. Study Design: Laboratory based experimental study. Duration and Place of Study: Department of Anatomy & Department of Pathology, Army Medical College Rawalpindi Pakistan, with the collaboration of National Institute of Health (NIH), Islamabad Pakistan, from Dec 2013 to Dec 2014. Methodology: Forty (n=40) adult BALBc female mice, having an average weight of 25-27gms. They were all in the pro-estrous phase. All were equally divided into four groups each containing 10mice. Group-A, was marked as control and kept for one month in standard atmosphere of animal house. Group-B was under immobilization stress for 06hrs/day by restricting them in locally made restrainers having 10 compartments each. Group-C was exposed to 100 decibels of noise stress of for 06hrs daily. Group-D was given hunger stress by diet control to average 3g of commercially pelleted food daily, which is around 50% of ad libitum food intake. Dissection of Animals was done after one month. For histological study ovaries were treated, fixed and stained. Graffian follicle diameter was measured. SPSS version 20 was used for statistical analysis. Results: mean values of graafian follicle diameters. Group-A showed statistically significant difference when compared with groups B (p-value <0.001) and D (p <0.005), however Group-C was insignificant (p=0.649). The comparison of Groups B with C (p-value <0.001) and D (p=0.039) showed statistically significant and Group-C and Group-D also had statistically significant difference as p-value <0.001. Conclusion: Diameter of graffian follicle was reduced..